A stunting profile of children younger than five years in selected vulnerable communities in Worcester, Breede Valley, Western Cape - Lenhoff, Annemie (Stellenbosch : Stellenbosch University, 2020)
Thesis (MNutr)--Stellenbosch University, 2020.